Proteomics a Key Tool for a Better Understanding of Endometriosis: - Nobakht Motlagh Ghochani, Bi bi Fatemeh; Gilany, Kambiz (Archives of Advances in Biosciences, 2011)
Endometriosis is a painful reproductive disease afflicting about up to 20% of women. It is one of the most frequent benign gynaecological diseases, however, little is known about the pathological of endometriosis. Over the past decade, high-throughput proteomics technologies have evolved considerably and have become increasingly more commonly applied to the investigation of female reproductive disease, including endometriosis. In this mini-review the authors look at the application of proteomics technologies in order to find biomarker associated with endometriosis.